The Relationship Between the Level of Knowledge of Young Women About Anemia and the Incidence of Anemia in Sigarang-Garang Village, Naman Teran District, Karo Regency in 2023 - Miftahul Jannah; Herianto Bangun (SEAN Institute, 2023)
This study aimed to assess the relationship between the knowledge of adolescent girls about anemia and its occurrence in Sigarang-Garang Village, Naman Teran Subdistrict, Karo District, in 2019. The pre-experimental research used a sample of 30 adolescent girls, revealing that a significant 70% had limited knowledge about anemia. Statistical analysis found a significant correlation between knowledge about anemia and its occurrence. The data further suggested that improving knowledge could potentially reduce the incidence of anemia. The study underscores the importance of educational interventions and outreach by healthcare professionals to bridge the knowledge gap and enhance the overall health of adolescent girls in the region.